Diagnostic dilemmas in the short rib - Polydactyly syndrome group - ELÇİOĞLU, HURİYE NURSEL (WILEY-LISS, 2002)
The short rib-polydactyly syndromes are a group of lethal skeletal dysplasias with autosomal recessive inheritance characterized by markedly short ribs, short limbs, usually polydactyly, and multiple anomalies of major organs. At least four types have been recognized. The radiological findings of 10 cases are presented. Each fetus or stiilbirth has some of the radiological features of the four established types of short rib-polydactyly syndrome and raises diagnostic dilemmas in differentiating these entities. The overlapping phenotypes of these fetuses supports the previously suggested hypothesis that the different subtypes of the short rib-polydactyly syndrome group are not single entities, but rather part of a continuous spectrum with variable expressivity. (C) 2002 Wiley-Liss, Inc.
Keywords: short rib-polydactyly; asphyxiating thoracic dystophy; (Jeune syndrome); chondroectodermal dysplasia (Ellis-van; Creveld syndrome); FACIAL-DIGITAL-SYNDROME; ASPHYXIATING THORACIC DYSTROPHY; ELLIS-VANCREVELD SYNDROME; CONTINUOUS-SPECTRUM; JEUNE SYNDROME; VERMA-NAUMOFF; DYSPLASIA; MOHR; PATIENT; INVERSION